The experimental comparison of parameters signals of acoustic emission during destructive test on composites based on cement - Hoduláková, Michaela; Kocáb, Dalibor; Topolář, Libor; Kucharczyková, Barbara (MATEC Web of Conferences, 2018)
The paper reports the analysis of acoustic emission signals captured during compressive strength tests of fine-grained cement-based composites of various composition. Acoustic emission monitoring belongs to a non-invasive and passive non-destructive testing technique. It is one of the most sensitive experimental techniques to monitor cracking of materials. While the acoustic emission phenomenon is directly associated with nucleation of cracks in materials based on cement, the measurement of these kinds of materials is readily applied to detect cracking activity. An understanding of microstructure–performance relationships is the key to true understanding of material behaviour.

The paper reports the analysis of acoustic emission signals captured during compressive strength tests of fine-grained cement-based composites of various composition. Acoustic emission monitoring belongs to a non-invasive and passive non-destructive testing technique. It is one of the most sensitive experimental techniques to monitor cracking of materials. While the acoustic emission phenomenon is directly associated with nucleation of cracks in materials based on cement, the measurement of these kinds of materials is readily applied to detect cracking activity. An understanding of microstructure–performance relationships is the key to true understanding of material behaviour.
The experimental comparison of parameters signals of acoustic emission during destructive test on composites based on cement
Keywords: -; -